Model data warehouse untuk Operasional petugas pemadam kebakaran Pada dinas pemadam kebakaran provinsi DKI Jakarta - Munawar, Kharis; Spits Warnars, Harco Leslie Hendric (Jurnal Ilmu Komputer, 2019)
In this paper we design 2 data warehouse design models for the DKI Jakarta fire department. The first data warehouse design model is categorized as a fact constellation schema, where there are 3 fact tables, 2 dimensional tables and 1 sub dimension table, while the second data warehouse design model is a fact constellation schema which consists of only 3 fact tables as well. Both of these data warehouse models are displayed with the intention that the implementation of the data warehouse based on the fire extinguisher data will look different and that will certainly be faster by using the 2nd model which is categorized as an non normal data warehouse model which only consists of 3 fact tables which the lack of a join process in the fact table and the dimensions of the data warehouse will speed up the query process in building the data warehouse report. The design model of the data warehouse is designed based on 4 excel table files, each of which has 1 table downloaded from the DKI Jakarta fire department's website on the website data.jakarta.go.id.